Prevalens dan faktor berkaitan jangkitan helmin tularan tanah dalam kalangan murid tahap satu sekolah rendah di jajahan Bachok, Kelantan - Roze, Mohamad Noor Mohamad (2016)
Ascaris lumbricoides, Trichuris trichiura, Necator americanus and Ancylostoma duodenale are soil-transmitted helminth that infect approximately onethird of the world human population who generally lives in poor communities of developing countries; and the helminthic problems are still unceasing among children living in Bachok district of Kelantan. The objective of this study was to determine the incidence of soil-transmitted helminthiases (STH) among level one (year one, two and three) schoolchildren in Bachok district. The associations between STH and the schoolchildren anthropometric measurements, haemoglobin concentrations, various demographic data, different socio-economic factors and also their hygienic practices associated with STH were also studied. In this study, two sub-districts of Bachok with beaches were randomly selected; in which all primary schools in Tawang and Telong sub-districts were recruited. Since Tawang district has more primary schools (4) than Telong (2), proportionate samplings were performed to obtain 68.9% and 31.1% of the targeted sample size of 270 level one schoolchildren from the two sub-districts, respectively. Formalin-ethyl acetate concentration technique was used to detect helminth ova and/or larvae in the stool samples. A portable haemoglobinometer (Hemocue HB 201+, Sweden) was used to determine capillary haemoglobin concentration from a drop of finger-pricked blood. The anthropometric measurement was taken from all the schoolchildren. Interview was conducted based on a previously validated structured questionnaire to obtain thedemography, socio-economic status and hygienic practices of the schoolchildren. About 22.2% (43/194) of the level one schoolchildren in Bachok district were found to be positive for STH. Fischer’s Exact Test chi-square analysis showed that there were no significant difference between STH and body mass index ( = 0.461, p<0.05) and capillary haemoglobin concentration ( = 0.764, p<0.05) among the level one schoolchildren in Bachok. However, Kendall’s tau-b analysis revealed that household with 7 or more family members were found to be significantly associated with STH ( = 0.017, p<0.05). In addition not washing hands with soap before meal ( = 0.045, p<0.05) was found to be significantly associated with STH. Negative associations were obtained between walking barefooted, drinking unboiled water and eating raw vegetable with STH. In conclusion, this study revealed that STH is still a health concern among growing-up children in Bachok. In future, it would be interesting to study the effect of reducing the significant unhygienic practices reported in this study to minimize the transmission of STH among level one schoolchildren in Bachok.